Living with technological challenges: does socioeconomic status affect people’s health? - Jia Xu; Chun Xia; Xiuzhen Ding (BMC Geriatrics)
Abstract Background Technological challenges in accessing medical care services may cause individuals to feel isolated from the medical care system. This study posits that individual’s subjective socioeconomic status (SES) contribute to differing levels of technological challenges when seeking medical care services, subsequently impacting their health conditions. Methods A questionnaire survey was administered to 1,932 residents in China (1,037 men, 891 women, and 4 missing; M age: 64.28 ± 11.30 years, range: 45–99 years). Participants included 792 urban (40.99%) and 1,140 rural (59.01%) residents. We measured SES, technological challenges perceptions, health conditions, and other control variables. Results Analysis of 10,000 bootstrapped samples revealed that technological challenges partially mediate the association between SES and health conditions. Moreover, rural people with low SES had poorer health because of technological challenges. This effect was not significant for urban people after controlling for sex, age, education level, marital status, and experience accessing medical care services. Conclusions SES significantly and negatively impacted individuals’ health conditions, especially for rural residents, owing to their technological challenges. This study provides evidence and insights into the nexus of policy formulation, modern technology, and public perceptions regarding shortcomings and risks in public health policies.